Propuesta de Sistematización en Power BI para la Generación, Proyección y Análisis de Estados Financieros del Supermercado La Casona (2025)
This research aims to develop a systematization in Power BI that automates the generation and projection of the financial statements of La Casona supermarket, located in Cúcuta. The research approach is mixed, in terms of the quantitative, it includes the analysis of the financial statements corresponding to the years 2021, 2022 y 2023, to evaluate the financial performance of the supermarket. In relation to the qualitative, two semi-structured interviews were conducted, with the manager and the tax advisor, to know about the internal processes and expectations regarding the proposed application.